Preliminary study of heavy metal (Zn, Pb, Cr, Ni) contaminations in Langat River Estuary, Selangor - Mokhtar, Nor Farhanna; Aris, Ahmad Zaharin; Sarva, Mangala Praveena (Elsevier, 2015)
Estuaries are the most productive area which generates a lot of organic matter. Due to its geographical and behaviour, they are potentially act as organic trap and can be a sink of pollutants especially metals ions. Therefore, a preliminary study on selected heavy metals (64Zn, 52Cr, 60Ni, and 208Pb) in sediments was conducted at 10 sampling stations along the Langat estuaries area. The aims of this study are to update the current status of metals ions and to illustrate the accumulation pattern of (64Zn, 52Cr, 60Ni, and 208Pb) in the sediment of Langat estuaries area. Metal concentration of sediment samples were analysed using flame Atomic Absorption Spectrophotometer (AAS). The concentrations of sediment ranged as followed: Zn (1.5-45.62 mg/kg), Cr (4.38-21.77 mg/kg), Ni (36.2-49.02 mg/kg) and Pb (6.8-36.68 mg/kg). However, concentrations of all trace elements were found below the threshold level stated in the Hong Kong Interim Sediment Quality Guideline (HK ISQG) except for concentration of Ni in sediment of station 2. Station 2 showed the highest concentration of Ni, Zn, Pb and Cr because it's received high metals pollution from the industrial and shipping activity which locates nearby the northern site of Port Klang. The output from this study will portray backgrounds contaminations of the selected metals in Langat river estuary and will be useful for the environmental management and policies